Factors influencing technology acceptance for ubiquitous public transportation services in tourism - Salam, Sazilah; Rusdi, Jack Febrian; Shafie, Norazlina; Ahmad Fesol, Siti Feirusz (Institute Of Advanced Engineering And Science (IAES), 2023)
This article discusses the factors that influence public transport users and the driver’s intentions towards ubiquitous features for public transport services. This study used convenience sampling for selecting tourists and a purposive sample to select bus drivers, taxi drivers, and trishaw pullers in Melaka, Malaysia, a popular tourist destination. The users' dataset contains three main results: factors influencing users' use of public transportation services, levels of user satisfaction with existing public transportation services, and elements influencing how often people choose to use the suggested ubiquitous features for public transportation services. The drivers' dataset, on the other hand, is divided into two primary sections: variables influencing drivers in delivering public transportation services and factors influencing drivers' adoption of the suggested ubiquitous features for public transportation services. The analysis included descriptive statistics on factors influencing users and drivers in using public transportation services, levels of user satisfaction with existing public transportation services, and factors influencing users' and drivers' adoption of proposed ubiquitous features for public transportation services. The findings can be used to investigate the demand for on-time delivery from public transport services